Assessment of Mangrove Ecosystem Degradation to the Population of Polymesoda erosa in Segara Anakan, Cilacap - Dyah Dwi Listyaningsih; Fredinan Yulianda; Erwin Riyanto Ardli (Universitas Muhammadiyah Surakarta, 2013)
Segara Anakan is a unique ecosystem with lagoons, mangrove and lowland. One of biota living in mangrove ecosystem is Polymesoda erosa. The species is valuable both economically and ecologically. This study aims to determine population of P. erosa and to analyze its relationship with mangrove degradation in Segara Anakan, Cilacap. Purposive Random Sampling was used to collect the clams data and plots sampling techniques were applied to obtain vegetation data. The result shows that there are very weak correlations between P. erosa and mangrove. Based on GIS analysis, mangrove area in Segara Anakan was 8036.9 ha. P. erosa str ongly cor r elates to envir onmental components namely water content of soil, temperature and light intensity. People utilized P. erosa as source of food, income and land hoard.